
0.25×6+0.6的简便运算?
34个回答
展开全部
0.25×6+0.6=0.25×6+6×1÷10=6×(0.25+1)÷10=0.6×1.25=0.75
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
0.25×6+0.6
=0.25×6+6×0.1
=6×(0.25+0.1)
=6×0.35
=2.1
=0.25×6+6×0.1
=6×(0.25+0.1)
=6×0.35
=2.1
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
0.25×6+0.6
=0.6×10×0.25+0.6
=0.6×(2.5+1)
=0.6×3.5
=2.1
=0.6×10×0.25+0.6
=0.6×(2.5+1)
=0.6×3.5
=2.1
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
0.25x6+0.6
=0.25x6+6x0.1
=6x(0.25+0.1)
=6x0.35
=2.1
=0.25x6+6x0.1
=6x(0.25+0.1)
=6x0.35
=2.1
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
展开全部
0.25×6+0.6
=1.5+0.6
=2.1
=1.5+0.6
=2.1
已赞过
已踩过<
评论
收起
你对这个回答的评价是?
推荐律师服务:
若未解决您的问题,请您详细描述您的问题,通过百度律临进行免费专业咨询